SIFO 1990: Environment barometer - Fläkt AB; Swedish Institute of Public Opinion Research (Swedish Institute of Public Opinion Research, 1993)
This survey was carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of Fläkt AB. The respondent was asked about interest in environmental issues, conversations with other people about how to improve environment, purchase of environmentally sound products and recycling of aluminium cans. Concern about different kind of environmental pollution. Confidence in various groups concerning environmental issues. Attitude toward environmental changes the next five years and environmental changes one generation ahead. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1988.

Denna undersökning utfördes av Svenska Institutet för opinionsundersökningar på begäran av Fläkt AB. Respondenterna fick frågor om hur intresserade de var av miljöfrågor, konversationer med andra personer om vad man kan göra för miljön, köp av miljövänliga produkter och återvinning av aluminiumburkar. Vidare frågades om deras oro om olika slags miljöförstöring, förtroende för olika grupper vad gäller miljöfrågor. Attityder gentemot miljöförändringar de kommande 5 åren och miljöförändringar en kommande generation. Bakgrundsvariabler inkluderar information om kön, bostadsort, ålder, svenskt medborgarskap, yrke, privat eller offentlig sektor, medlemskap i fackförening, röstningsvana, preferens av politiskt parti samt det parti man röstat för 1988.
SIFO 1990: Miljöbarometer
Keywords: Environment and conservation; Miljö och naturvård; Social Sciences; Samhällsvetenskap